HYPONATREMIA AND ITS CORRELATION WITH HEPATIC ENCEPHALOPATHY IN PATIENTS WITH CIRRHOSIS LIVER - Afridi, Muhammad Abdur Rahman; Ali, Zafar; Muhammad, Riaz; Asghar, Muhammad; Faheem Afridi, Muhammad; Bakkar Alam, Abu; Alam, Intekhab (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine hyponatremia and its correlation with hepatic encephalopathy in liver cirrhosis patients in a teaching hospital. Methodology: A descriptive study was carried out from April 2013 to May 2014, in the Department of Medicine, Lady Reading Hospital, Peshawar. The study included 130 patients with liver cirrhosis. Hyponatremia was identified among these. Hepatic encephalopathy (HE) was diagnosed and graded according to the West Haven classification into four grades. For data entry and analysis, SPSS version 21.0 was utilized. Spearman rank test was used for determining the relationship of hyponatremia and severity of hepatic encephalopathy. Results: Of the 130 patients, males were 76 (58.5%) and females were 54 (41.5%). Mean age of study patients was 55.52 ±10.144 years. Hyponatremia was present in 48 (36.9%) patients. Mild Hyponatremia was present in 12 (9.2%), Moderate in 28 (21.5%) and Severe in 8 (6.2%) patients. Hepatic encephalopathy was present in 88 (67.7%) patients. Hepatic encephalopathy grade I was present in 27 (20.8%), grade II in 31 (23.8 %), grade III in 16 (12.3 %), and grade IV in 14 (10.8%) patients. In 48 patients with hyponatremia, 42 were found to have HE (r =0.32, p value <0.001). Correlation of severity of hyponatremia with grades of HE showed (r =0.33, p value <0.001). Conclusion: Hyponatremia was found with increased frequency in patients with cirrhosis liver. The relationship of hyponatremia with frequency and severity of hepatic encephalopathy was statistically significant.